The lady from Zagreb [compact disc, unabridged] - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2015)
A beautiful actress, a rising star of the giant German film company UFA, now controlled by the Propaganda Ministry. The very clever, very dangerous Propaganda Minister ... close confidant of Hitler, an ambitious schemer and flagrant libertine. And Bernie Gunther, former Berlin homicide bull, now forced to do favors for Joseph Goebbels at the Propaganda Minister's command.